1986
DOI: 10.1021/bi00366a023
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of the conformations and interactions of substrates and ribonucleotide templates bound to the large fragment of DNA polymerase I

Abstract: The large fragment of DNA polymerase I (Pol I) effectively uses oligoribouridylates and oligoriboadenylates as templates, with kinetic properties similar to those of poly(U) and poly(A), respectively, and has little or no activity in degrading them. In the presence of such oligoribonucleotide templates, nuclear Overhauser effects (NOE's) were used to determine interproton distances within and conformations of substrates bound to the large fragment of Pol I, as well as conformations and interactions of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 53 publications
(101 reference statements)
3
33
0
Order By: Relevance
“…Moreover, Mildvan also suggested the existence of what we call the prechemistry avenue: "an error prevention or verification step is needed, which follows the binding of the substrate and precedes the primer elongation step" (74). He further proposed that coordination of the enzymebound metal by the β-phosphate is the key step in activation of the chemical reaction (74,76,77).…”
Section: Prechemistry Avenuementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Mildvan also suggested the existence of what we call the prechemistry avenue: "an error prevention or verification step is needed, which follows the binding of the substrate and precedes the primer elongation step" (74). He further proposed that coordination of the enzymebound metal by the β-phosphate is the key step in activation of the chemical reaction (74,76,77).…”
Section: Prechemistry Avenuementioning
confidence: 99%
“…He further proposed that coordination of the enzymebound metal by the β-phosphate is the key step in activation of the chemical reaction (74,76,77). That competing pathways spur evolution of the active site geometry slowly in a substratedependent context (i.e., depending on correct vs incorrect base present) presents an intriguing mechanism for pol β's regulation of fidelity.…”
Section: Prechemistry Avenuementioning
confidence: 99%
“…In the first reports on KF, it was suggested that the first conformational change may reflect reorientation of the triphosphate moiety of the incoming nucleotide to interact with side chains of the enzyme (28). This hypothesis was put forward to explain the observation made by Mildvan and colleagues that the orientation of the triphosphate and its interaction with divalent cation change in a KF ternary complex (38,39). Recently, it has been suggested that the conformational change defined kinetically may be related to changes in the orientation of the fingers subdomain observed crystallographically (12,40,41).…”
Section: Conformational Changes During 3d Pol -Catalyzed Nucleotide Imentioning
confidence: 99%
“…79 The importance of the -phosphate coordination in the assembly of polymerase active site for catalysis was also noted by Mildvan and co-workers. 80 Magnesium Ions Rearrangement. DNA polymerases across the different families have common two-metal ion coordination with few conserved acidic residues (e.g., two highly conserved aspartate residues and possibly either another aspartate or glutamate) in the enzyme active site.…”
Section: Orchestrated Order Of Events During Pol Closingmentioning
confidence: 99%